Utilization of Sesai as an Environmentally Friendly Planting Media: Case Study of Buruk Bakul Village, Bukit Batu Subdistrict, Bengkalis Regency, Riau - Fadliyati, Refo; Sumiarsih, Eni; Budijono, Budijono (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2025)
Indonesia has abundant natural resources, including the Bengkalis coastal area. Bengkalis waters are the largest in Riau Province, with a water area of 677,472.44 km2. One of the coastal areas is Buruk Bakul Village in Bukit Batu District, Bengkalis Regency, which has an area of about 68.05 km2. However, when viewed from the condition of the waters, marine debris poses a threat. Organic waste or sesai inhibits the growth of mangrove saplings and even causes death in mangrove saplings. The location of the research object is the coast of Buruk Bakul Village. The research objectives are to determine the potential of sesai to be used as an organic planting medium and to know the community's social perceptions and economic perceptions towards sesai as a planting medium. The research method used in this research is the survey method. Primary data included the results of NPK analysis on sesai, questionnaires, interviews, and observations in the field. Purposive sampling was carried out using the Geographic Information System (ArcGIS) along the coast of Buruk Bakul Village to measure sesai potential. The analysis results show the abundant potential of sesai, which can increase utilization into environmentally friendly planting media with the availability of a total volume of sesai of 39,029.5 m³ with an average volume per location of 2,295.8 m³. NPK content analysis (0.41%, 19.44 mg/100g, and 21.84 mg/100g) can be used as planting media. Social perception showed community initiative through survey results, which showed that 64% of respondents responded well. Economic perception by utilizing sesai as a planting medium can provide a profit of IDR.3,000 per unit, opening up opportunities for increased income for the people of Buruk Bakul Village